Apicoectomy: A review of clinical concepts and techniques - Vivek Thakur; Rahul Kaul (Journal of Oral Research and Review)
Apicoectomy is the surgical approach for preserving a tooth with a large periapical lesion which may not be treated with traditional therapy. The goal of apicoectomy is to seal off the root canal system, promoting healing by establishing a barrier between the irritants inside the canal and the periapical tissue. Apicoectomy is a predictable, less expensive alternative to tooth extraction and replacement when done after proper case selection. Locating areas in the root apex that have not been sealed and then appropriately sealing the root apex are crucial steps in apicoectomy. The effectiveness of surgical endodontic therapy has increased as a result of the application of microsurgical tools and techniques. Using a surgical microscope during an apicoectomy is recommended because it provides superior focused illumination of microstructures and enables clear view of the operative field with high magnification. Moreover, lasers and guided microsurgery in apicoectomy provide enhanced periapical healing with a favorable long-term prognosis. The current review describes basic concepts and advanced techniques used for apicoectomy.